Team Game Tournament Learning with Online Comic Media Improves Students' Wrehastra Script Writing - Sadwika, I Nyoman; Liska, Luh De; Dewi, Ni Pt. Pande Mirah Surya; Parwati, Ni Putu Yuniarika (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Based on the initial reflection at SMK Negeri 1 Sukawati, it was found that there was a problem, namely the low ability of grade X DKV 2 students at SMK Negeri 1 Sukawati to write Wrehastra script. Based on interviews with Balinese language teachers, this was also caused by the lack of innovative learning models that were suitable for the students' learning climate. The purpose of this study is to determine the effectiveness of the TGT (Team Game Tournament) cooperative learning model using Balinese online comic media in improving student learning achievement and response. Data was collected using interview, observation, and test methods, then analysed using descriptive statistical methods. The research design consisted of N-cycles comprising (1) planning stage, (2) action implementation stage, (3) observation stage, and (4) reflection stage. The TGT (Team Game Tournament) cooperative learning model assisted by Balinese online comic media can improve the ability to write Wrehastra script among students in class X DKV 2 at SMK Negeri 1 Sukawati in the 2023/2024 academic year. This is evidenced by the average test results in Cycle I of 64.75 or 30.7% with a satisfactory rating, and an increase in Cycle II to 83.49 or 96.1% with a good rating. Responsiveness also improved, as evidenced by the average score in Cycle I of 69.15 or 34.6% with a satisfactory rating, which increased in Cycle II to 83 or 96.1% with a good rating.